Investigation of the effect of plasma waves excitation on target normal sheath ion acceleration using fs laser‐irradiating hydrogenated structures. Issue 8 (3rd April 2019) - Torrisi, L.; Cutroneo, M.; Torrisi, A.; Rosinski, M.; Zaras‐Szydlowska, A.; Parys, P.
Abstract : Measurements of ion acceleration in polymethylmethacrylate foils covered by a thin copper film irradiated by fs laser in target normal sheath acceleration regime are presented. The ion acceleration depends on the laser parameters, such as the pulse energy; depends on the irradiation conditions, such as the focal point position of the laser with respect to the target surface; and depends on the target properties, such as the metallic film thickness. The proton acceleration increases in the presence of the metallic film enhancing the plasma electron density, reaching about 1.6 MeV energy for a focal position on the target surface. The plasma diagnostics uses SiC detectors, absorber foils, Faraday cups, and gafchromic films. Employing p‐polarized laser light and a suitable oblique incidence, it is possible to increase the proton acceleration up to about 2.0 MeV thanks to the effects of laser absorption resonance due to plasma waves excitation.